Pharmacokinetics and phenotyping properties of the Basel phenotyping cocktail combination capsule in healthy male adults. Issue 2 (12th December 2019) - Suenderhauf, Claudia; Berger, Benjamin; Puchkov, Maxim; Schmid, Yasmin; Müller, Sabine; Huwyler, Jörg; Haschke, Manuel; Krähenbühl, Stephan; Duthaler, Urs
Abstract : Aims: We compared the phenotyping metrics of a combination capsule formulation to its individual components of the newly composed Basel phenotyping cocktail. Moreover, we investigated a reduced sampling regimen for clinical applications. Methods: We performed in vitro experiments and a crossover pharmacokinetic study in twelve healthy male subjects to compare the Basel phenotyping cocktail capsule containing 6 cytochrome P450 (CYP) probe drugs with individual administration of the same drugs. Parent compounds and selected metabolites were determined by liquid chromatography–tandem mass spectrometry. Metabolic ratios (MR) for are under the curve (AUC) and single time point measurements and their correlation were determined. Results: Experiments with human liver microsomes and primary human hepatocytes in 3D co‐culture confirmed that flurbiprofen is a suitable CYP2C9 substrate. Both cocktail formulations (capsule and individual probe drug administration) were well‐tolerated and yielded reproducible MRs, which were almost identical. Correlations between single time point ratios and the corresponding AUC ratios depended on the sampling time point and the concentration time curve of the probe drugs. The MR of the capsule (Spearman rank correlation coefficient, Rs : 0.77–0.97) as well as the individual components (Rs : 0.69–0.99) correlated best at 6 h post‐treatment considering all 6 CYPs. Moreover, the 2‐h time points of the capsule agreed suitably with the AUC; however, the MR of omeprazole could not be determined for 10 out of 12 subjects. Conclusion: The capsule is easy to swallow, well tolerated and provides reliable estimates for CYP activity. The optimal sampling point for the capsule formulation is 6 h after intake.